White-Collar Crime - Goldstraw-White, J. author. aut Link
XI, 229 p.
Keywords: This book explores the accounts given by white-collar crime offenders to defend their criminal behaviour in order to preserve their characters and social standing. It is based on in-depth interviews with 41 male and female convicted white-collar offenders, who were still serving their sentences in English prisons. Whilst a number of texts have been written about white-collar crime offenders, very few studies have attempted to approach this by examining the actual reasons and motives for their criminal behaviour directly from the offenders. This book aims to make further progress in this area. By exploring the participants' motives, opportunities and morality, this book will make a key contribution to exploring white-collar crime offenders' perspectives of their crimes. This book not only adds to the academic knowledge in this area, but also helps organizations to consider the strengths of their crime prevention methods and appropriateness of their fraud and security policies.